Teatr w filmie. Dramat "Brat naszego Boga" Karola Wojtyły w interpretacji Krzysztofa Zanussiego = Theatre in celluloid. Krzysz tof Zanuss i?s interpretation of Karol Wojtyla`s "Our God`s Brother" - Bednarczyk-Stefaniak, Emanuela (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
At the beginning of the article Karol Wojtyla`s drama "Our God`s Brother" is shown as a cultural good that inspired another artist to speak through it about the problem of being born and growing up as a man with religious vocation. The main purpose of the paper is to present Krzysztof Zanussi`s view on the literary attempt to express the inner truth of Adam Chmielowski (Saint Brother Albert) by young Karol Wojtyla, experiencing his own problem related to the mystery of his calling to the priesthood.
Keywords: Jan Paweł II, papież (1929-2005); dramat polski-20 w.; film polski; Zanussi, Krzysztof (reżyser; 1939- )